The preference of migratory waterbirds to winter at a key location on the East Asian-Australasian flyway and its implications for habitat conservation - Shuangliang Dai; Yanyan Zhou; Jingsi Gao; Guowei Cheng; Linlin Wang; Haiyan Bai; Xiaoyu Lei; Hualin Xu; Xian-zhong Mao (Ecological Informatics)
Understanding the preference of migratory waterbirds to inhabit key habitats is crucial for mapping out effective management strategies to maintain migration network connectivity. This study investigated the attractiveness of Shenzhen Bay in southern China, a key site on the East Asian-Australasian Flyway Site Network, to migratory waterbirds. The abundance of migratory waterbirds in January remained stable at around 45,000 from 1996 to 2015, with fluctuations of about ±5000, and decreased after 2015, with an average annual decrease of around 2130 until 2021. The preference of waterbirds to inhabit Shenzhen Bay was primarily affected by local human activities and the climate in southern China. When the proportion of freezing weather (FP) in southern China exceeded 10 % (indicative of normal and harsh winter), the abundance of migratory waterbirds in Shenzhen Bay varied exponentially with FP. When the FP exceeded 36 % (harsh winter), freezing weather became the dominant factor influencing waterbird wintering. Consequently, Shenzhen Bay served as a crucial refuge for migratory waterbirds from higher latitudes. However, compared to other waterbirds, the black-faced spoonbill demonstrated stronger adaptability to harsh winters. In warmer and normal winters (FP < 36 %), protected areas were effective in resisting high anthropogenic pressure. However, when the human population density and relative nighttime light intensity in the Shenzhen Bay area exceeded certain thresholds, the effectiveness of protected areas declined. This was the main reason for the decline in migratory waterbird abundance in Shenzhen Bay after 2015. Therefore, to protect and maintain the attractiveness of Shenzhen Bay to migratory birds, it is necessary to implement more effective management and control human activities, for example, by establishing a 2-km buffer zone around the habitat. Our findings are significant for the protection of crucial habitats for migratory waterbirds in Shenzhen Bay, as well as in other similar key habitats within migratory waterbird flyway site networks.